PENGGUNAAN ANALISIS PONT PADA POPULASI MAHASISWA SUKU MINANG DI FAKULTAS KEDOKTERAN GIGI UNIVERSITAS ANDALAS - Maya Syafitri; Murniwati Murniwati (Andalas Dental Journal, 2013)
Dental cast analysis is one of the important thing in orthodontic treatments. One of the dental cast analysis which is usually used is Pont analysis, proposed in 1909. Pont did his research to a population in French which is Caucasian and stated that his theory needs to be tested to another ethnics to verify the applicability of Pont analysis to that population. On each race, there are some specific physical characteristics such as the form and width of dentition and dental arch. Minang population are Mongolian who has the different characteristics of dentition and dental arch with the Caucasians.The aim of this study is to identify whether Pont analysis is precise to be used to Minang population. Method : Cross-sectional design was used in this study. This study was done to 65 upper dental casts from Minang student at the Faculty of Dentistry Andalas University who met the inclusion criteria. The difference between the measured and the calculated interpremolar and intermolar arch width was tested with paired T test with the significant value of 0.05 (p=0.05). Result : Mean value of interpremolar width was 37.8838 ± 2.29042 mm and intermolar width was 47.6046±3.18780 mm. The result of statistical analysis showed that there is no significant differences of the measured and the calculated interpremolar and intermolar width of Minang Student at Faculty of Dentistry Andalas University (p>0.05). Conclusion : Pont analysis can be used as one of the dental cast analysis in orthodontic diagnosis and treatment planning to Minang population. It is suggested to do a further research to identify lower dental arch form of the Minang population whose upper dental arch width equals to the predicted arch width according to Pont’s formula.